Tool eccentricity in friction stir welding: a comprehensive review. (18th August 2019) - Shah, L. H.; Walbridge, S.; Gerlich, A.
ABSTRACT: This paper reviews research on the effect of tool eccentricity in the friction stir welding process. A distinction between pin profile eccentricity and tool eccentricity is addressed, followed by an in-depth review of the research progress in both of the cases, including the mechanism behind the eccentric motion and how it influences the overall joint outcome. Suggestions are made regarding potential future works in this field.